The relationship between body mass index (BMI) with the distance of the skin-epidural space in 3rd and 4th lumbar epidural anesthesia in nonobstetric surgery of Indonesian patients - Sri Rahardjo, Agung Sutrisno Yusmein Uyun (Universitas Gadjah Mada, 2012)
Skin to epidural space distance varies in an insertion of epidural needle which can greatly affectthe identification of the epidural space and epidural anesthesia complications. Therefore, acareful prediction of skin to epidural space distance is needed in doing insertions. The purposeof this study was to evaluate the relationship between body mass index (BMI) and the distanceof skin to the epidural space in the 3rd â 4th lumbar epidural anesthesia in nonobstetric surgery ofIndonesian patients. This was a prospective observational study with cross sectional designinvolving patients of both sexes between the age 18-65 years with ASA physical status I-II whounderwent non obstetric surgery with 3rd-4th lumbar epidural anesthesia in Dr. Sardjito GeneralHospital, Yogyakarta and in Satellite Hospital. Weight, height and BMI were considered as theindependent variables, whereas skin to epidural space distance was considered as dependentvariable. Data were collected and analyzed using multiple regression analysis continued usingPearsonâs correlation test to evaluate the relationship between BMI and skin to epidural spacedistance. One hundred patients selected from October to December 2011 were evaluated in thisstudy. The mean of weight, height and BMI were 57.35Â±11.59 kg, 155.98Â±5.88 cm and23.52Â±4.26 kg/m2, respectively. The mean of skin to epidural space distance of non obstetricsurgery of Indonesian patients was 40.89Â±9.95 mm. Multiple regression analysis showed thatBMI had a strongest relationship (r= 0.81; p<0.03) with skin to epidural space distance comparedto weight (r= 0.11; p=0.78) and height (r= 0.04; p<0.83). Further analysis using Pearsoncorrelation test showed that a significantly good correlation of BMI (r=0.92; p=0.001) andbody weight (r=0.87; p=0.001) with the skin to epidural space distance were observed. Inconclusion, BMI and body weight have a significant correlation with the skin to epidural spacedistance in non obstetric surgery patient.Â